The role of nutrient balance in shaping plant root-fungal interactions: facts and speculation. (June 2019) - Fabiańska, Izabela; Sosa-Lopez, Esperanza; Bucher, Marcel
Graphical abstract: Highlights: Bidirectional exchange of nutrients stabilizes mutualistic plant-fungal symbioses. Imbalance in nutrient status affects plant physiology and plant interactions with beneficial soil fungi. Molecular cross-talk between nitrogen and phosphorus essential for plant growth could have implications on root-microbiota interactions. Reconstructing plant nutritional status could support breeding of crops adept in establishing mutualistic symbiosis with fungal endophytes. Abstract : Microbiota colonizing plant roots and their vicinity were shown not to be just random associations, but compose, at least to some extent, host-selected microbial consortia. The plant physiological status, especially the nutrient status, prompts changes in plant morphology and metabolism, which successively imposes a selective pressure on microbial communities. It is well established that a low phosphate status of the host plant activates the molecular machinery underlying the development of mutualistic associations in the host root with arbuscular mycorrhizal fungi (AMF). We hypothesize that the plant´s response to changing nutrient stoichiometry affects processes at the root-mycosphere interface which promote or repress also root interactions with microbial taxa other than AMF. As a consequence, fundamental mechanisms underlying these interactions would be shared in AM host and non-host plants. A detailed understanding of the processes involved in maintenance of plant nutrient homeostasis could contribute to novel strategies in tailoring predominantly parasitic or commensalistic plant–microbe interactions towards beneficial associations.